Various types of extended spectrum β-lactamases: a literature review - Rastuti, Made Rina; Budayanti, Ni Nyoman Sri; Dwija, Ida Bagus Nyoman Putra (Journal of Clinical Microbiology and Infectious Diseases, 2023)
The inappropriate use of antibacterials causes the spread of resistance in bacteria and increases the health burden of infection due to the nature of resistance to many classes of antibiotics which are referred to as multi-resistant (multidrug resistant). Extended spectrum β-lactamase (ESBL) is one of the enzymes that cause multi-resistance, where bacteria with this enzyme become resistant to third-generation cephalosporin antibiotics which are often used to treat gram-positive and gram-negative bacterial infections in humans with minimal side effects. β -lactamase is an enzyme capable of hydrolyzing the β-lactam ring in β -lactam class antibiotics so that antibiotics become inactive. Mutations in the gene that encodes this enzyme produce a β-lactamase enzyme which can break down the β-lactam ring in all penicillin and cephalosporin antibiotics. The classification of β-lactamases is complex due to genetic, biochemical properties, and substrate affinity for β-lactamase inhibitors. There are also various types of ESBL enzyme-coding genes including TEM, SHV, CTX-M, VEB, PER, OXA, SFO-1, BEL-1, BES-1, TLA-1, and GES. This study aims to review various types of extended-spectrum β-lactamases.